Holy brothers: geography, kinship, and priesthood in ancient Israel - Rasure, Matthew R. (Lexington Books/Fortress Academic, 2024)
"Through the lenses of geography, kinship, and priesthood, this book brings into focus varied biblical materials related to Israel's early priesthood. With the tools of Documentarian narrative analysis and literary genealogies, Matthew R. Rasure delves deep into the memories of Aaron and Moses and the invention of their brotherhood"--